Development of a Tyrosinase Amperometric Biosensor Based on Carbon Nanomaterials for the Detection of Phenolic Pollutants in Diverse Environments. Issue 24 (23rd December 2022) - Liu, Yanran; Chen, Yafei; Fan, Yining; Gao, Guanyue; Zhi, Jinfang
Abstract: Phenolic compounds are widespread water contaminants with high toxicity and chronic carcinogenicity, whose concentration is restricted by a variety of water quality regulations. In the present study, we developed a tyrosinase biosensor based on a nanocomposite of carbon nanotubes, nanodiamonds, and soluble starch to enhance sensing performance during practical application. Doping nanodiamonds in soluble starch considerably improved the electrode's biocompatibility and electroactive sites, while carbon nanotubes improved the loading capacity and electron transfer efficiency of tyrosinase. The as‐prepared biosensor exhibited a broad detection range from 0.01 μM to 50 μM for phenol, which covered the concentration thresholds of the water standard requirement between drinking water to industrial effluents, and the limit of detection (LOD) is down to 2.9 nM. Furthermore, a portable instrument with an integrated probe and self‐calibrated algorithm software was developed to automatically detect and readout the phenol concentration. The as‐prepared instrument demonstrated good agreement to the ISO 4‐Aminoantipyrine spectrometric method in the phenol detection of wastewaters that was collected from a coal factory, chemical and biological manufacturing plants, and biological fermentation factory. The application of this novel biosensor and instrument are paving the way to a wider application of amperometric biosensors for in‐field phenol monitoring. Abstract : An amperometric biosensor based on carbon nanomaterials was developed showing a broad detection range in drinking water and industrial effluents.